Gambaran Tingkat Stres Akademik Mahasiswa Tingkat Akhir Prodi Kesehatan Masyarakat UNDANA - Lidia Danu; Afrona E. L. Takaeb; Sarci Magdalena Toy (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Academic stress is one of the stresses in college students. This type of research is descriptive quantitative research. This study aims to explain the description of the academic stress level of final year students of the Public Health Study Program. The population in this study was 770 and the number of samples used was 202 students using random sampling technique. The results of this study indicate that based on the academic stress level of final year students, most respondents experienced a high level of academic stress 97 respondents (48%). Respondents experienced high academic stress due to difficulty determining research themes, confusion about choosing to meet supervisors and pressure from parents. Based on the characteristics of the level of academic stress, most respondents experienced high academic stress that occurred at the age of 24 years (30.2%), because some respondents had the same academic stress when doing their final project. Respondents who are female experience high academic stress (71%), and high levels of academic stress occur in semester 14 (28.7%). Based on the characteristics of the level of academic stress that most respondents experience high academic stress that occurs on. Based on the factors causing the level of academic stress, most of them have a high score, namely frustration (57.92%), caused by difficulty determining the research theme and difficulty finding sources according to the research theme, conflict (58.42%) because it is difficult to determine the choice to complete the final project, pressure (58.42%), caused by pressure from parents, pressure (58.42%), due to pressure from parents, and pressure from lecturers to complete assignments on time, changes (54.46) due to respondents having difficulty adapting to the learning system which usually lectures according to the schedule of the lecturer but when doing the final project the time is irregular, and self-imposition (52.42%) due to respondents doing the final project by force so that they are easily tired and stressed.